Implementasi Aplikasi Zahir Accounting Versi 6.0 Dalam Pengolahan Data Keuangan Saung Boneka ADW - Novianda, Widiya; Agustini, Fajar (Program Studi Sistem Informasi Akuntansi Kampus Kota Sukabumi, 2022)
The important role of information technology has an influence on the business world. Work or activities related to business will be easier by utilizing an effective and efficient work system, especially related to accounting information systems. The increasing number of business applications that are able to meet the needs of business actors in processing financial data quickly, one of which is Zahir Accounting version 6.0. ADW Tirtamulya Doll Saung does not process financial data, so it is difficult for business actors to know the development of their business. For this reason, the author aims to implement financial data processing at Saung Doll ADW Tirtamulya using the Zahir accounting application version 6.0 in this study. The research method used is a case study method of processing financial data using the Zahir accounting application with data collection methods used including observation, interviews and literature study. The results of the research that the author did show that business actors can see information on the development of their business from the resulting financial data. Financial data processing can be done quickly, supported by facilities that are very easy to understand, so that the financial data processing process runs effectively.